2022
DOI: 10.47535/1991auoes31(1)012
|View full text |Cite
|
Sign up to set email alerts
|

Social Responsibility Practices and Orientations of Romanian Smes – Case Study in Bihor County

Abstract: This paper investigates the forms, areas and orientations of social responsibility (SR) within small and medium enterprises (SMEs) in Bihor County, Romania. Acknowledging the particularities of SMEs involvement in social and environmental actions, we investigate both the practices and orientations of these firms from our region in SR. Our study, based on the responses of 52 owner-managers of SMEs, reveals interest towards SR practices, yet a limited visibility of such actions. The orientations towards SR can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The only study on CSR disclosure on websites by companies active in Romania that has been identified belongs to Saveanu and Abrudan (2015) and is rather limited in scope. The paper focused mainly on the companies operating in the county of Bihor (in Western Romania) and has included some 50 companies outside that geographical area, which have been selected from a list put together by a local publication.…”
Section: Introducing the Research Rationalementioning
confidence: 99%
“…The only study on CSR disclosure on websites by companies active in Romania that has been identified belongs to Saveanu and Abrudan (2015) and is rather limited in scope. The paper focused mainly on the companies operating in the county of Bihor (in Western Romania) and has included some 50 companies outside that geographical area, which have been selected from a list put together by a local publication.…”
Section: Introducing the Research Rationalementioning
confidence: 99%